Paraganglioma with a very rare presentation - Manika Khare; Manish Kumar Gupta; Umesh Babu Sharma; K M Garg (Wolters Kluwer Medknow Publications, 2018)
Paragangliomas (PGLs) are rare tumors of neural crest origin, with a malignancy rate of approximately 10% and a 5-year survival rate of <50%. We present a case of malignant PGL arising from the porta hepatis with metastasis to the portal lymph node and bilateral ovaries. PGLs arising from the porta hepatis are very rare. As per our knowledge, only three cases of hepatic duct PGL have been reported. It is important to detect it earlier because the treatment modality and prognosis of benign and malignant PGL differs and defines the prognosis of the patient.